Tracing the Distribution of European Lactase Persistence Genotypes Along the Americas ... : تتبع توزيع الأنماط الجينية الأوروبية لاستمرار اللاكتاز على طول الأمريكتين ... - Ana Cecília Guimarães Alves; Natalie Mary Sukow; Gabriel Adelman Cipolla; Marla Mendes de Aquino; Thiago P. Leal; Maria Luiza Petzl‐Erler; Ricardo Lehtonen Rodrigues de Souza; Ilíada Rainha de Souza; César Sánchez; Meddly L. Santolalla; Douglas Loesch; Michael Dean; et al. (OpenAlex, 2021)
In adulthood, the ability to digest lactose, the main sugar present in milk of mammals, is a phenotype (lactase persistence) observed in historically herder populations, mainly Northern Europeans, Eastern Africans, and Middle Eastern nomads. As the –13910 ∗ T allele in the MCM6 gene is the most well-characterized allele responsible for the lactase persistence phenotype, the –13910C > T (rs4988235) polymorphism is commonly evaluated in lactase persistence studies. Lactase non-persistent adults may develop symptoms of lactose intolerance when consuming dairy products. In the Americas, there is no evidence of the consumption of these products until the arrival of Europeans. However, several American countries' dietary guidelines recommend consuming dairy for adequate human nutrition and health promotion. Considering the extensive use of dairy and the complex ancestry of Pan-American admixed populations, we studied the distribution of –13910C > T lactase persistence genotypes and its flanking haplotypes of ... : في مرحلة البلوغ، تكون القدرة على هضم اللاكتوز، وهو السكر الرئيسي الموجود في حليب الثدييات، نمطًا ظاهريًا (استمرار اللاكتاز) لوحظ في مجموعات الرعاة تاريخيًا، وخاصة الأوروبيين الشماليين والأفارقة الشرقيين والبدو الرحل في الشرق الأوسط. نظرًا لأن الأليل -13910 * T في جين MCM6 هو الأليل الأكثر تميزًا المسؤول عن النمط الظاهري لاستمرار اللاكتاز، فإن تعدد الأشكال –13910C > T (rs4988235) يتم تقييمه بشكل شائع في دراسات استمرار اللاكتاز. قد يصاب البالغون غير الدائمين بأعراض عدم تحمل اللاكتوز عند استهلاك منتجات الألبان. في الأمريكتين، لا يوجد دليل على استهلاك هذه المنتجات حتى وصول الأوروبيين. ومع ذلك، توصي المبادئ التوجيهية الغذائية للعديد من البلدان الأمريكية باستهلاك منتجات الألبان من أجل التغذية البشرية الكافية وتعزيز الصحة. بالنظر إلى الاستخدام المكثف لمنتجات الألبان والأصل المعقد للسكان المختلطين في عموم أمريكا، درسنا توزيع الأنماط الجينية لاستمرار اللاكتاز -13910C > T وأنماطها الفردية الجانبية ذات الأصل الأوروبي في 7428 فردًا من العديد من السكان المختلطين في عموم أمريكا. وجدنا أن تواتر الأليل –13910 * T في ...